Complex compound of trinitrotriamminecobalt(III): in theoretical studies - Rokhim, Deni Ainur; Asrori, Muhammad Roy; Wijaya, Husni Wahyu (Eclética Química, 2024)
[Co(NH3)3(NO2)3] is an octahedral complex compound that can have several isomers. The complex compound has magnetic properties. Its stability has been explained. It can be easily synthesized and is known as a bioinorganic synthesis reagent, oxidant compound and base hydrolysis.